A NEW SPECIES OF DIASTEMA (GESNERIACEAE) FROM THE EASTERN ANDEAN SLOPES OF PERU. (21st March 2020) - Clark, J. L.; Moonlight, P. W.
Abstract : A striking new species of Diastema, D. fimbratiloba, is described from Ucayali Region, along the eastern Andean slopes in central Peru. The new species has a fimbriate lower corolla lobe, a feature not previously documented in the genus. We also provide a general comparison of the newly described species and morphologically related species in the context of the taxonomy and phylogeny of the poorly known genus Diastema .